Molecular Characterization of Banana (Musa AAB Plantain Subgroup) Clones - Simi S (Department of Pomology and Floriculture, College of Agriculture, 2001)
Attempts were made for characterizing eleven banana (Musa AAB Plantain subgroup) clones at molecular level during January 2000 to October 2001 at the Department of Pomology and Floriculture and the Plant Molecular Biology and Biotechnology Centre, College of Agriculture, Vellayani. Tissues from fully unfurled leaves of the clones, were used for isolating DNA, using modified Walbot's method. Storage of leaves at -SYC did not affect either the DNA yield or purity ratio. Gel elctrophoresis using agarose concentrations of 0.09 per cent and 1.4 per cent were the best for visualizing the genomic DNA and RAPD pattern, respectively. The best voltage level was 75 V. TBE buffer could produce better separation of bands compared to TAE buffer. Twenty nanogram of DNA, 200 IlM each of dNTPs, 0.6 units Taq DNA polymerase and 5 pM primer in presence of the assay buffer gave good PCR amplification results. The programme consisted of an initial denaturation at 95°C for 3.0 minutes, followed by 45 cycles of denaturation at 95°C for 1.0 minute, annealing at 36°C for 1.0 minute 30 seconds and extension at 72°C for 2.0 minutes. The synthesis step of the final cycle was extended further by 6.0 minutes. The products of .ampl ification were kept at 4.0°C until attended. One hundred and six RAPDs were generated when PCR amplification was carried out using forty decamer primers (Operon Inc., CA, USA) of kit A and kit B. Of these, 100 bands were polymorphic which accounted to an average of 2.5 polymorphic bands per primer. Eight primers (OPA-OI, OPA-03, OPA-13, OPB-OI, OPB-06, OPB-lO, OPB-12 and OPB-IS) produced reproducible banding patterns on at least two runs. These primers yielded 42 scorable bands with an average of 5.25 bands per primer. The amplification